1998
DOI: 10.1038/sj.bjp.0701979
|View full text |Cite
|
Sign up to set email alerts
|

Complete in vivo reversal of P‐glycoprotein pump function in the blood‐brain barrier visualized with positron emission tomography

Abstract: 1 Homozygously mdr1a gene disrupted mice (mdr1a(7/7) mice) and wild type mice (mdr1a(+/+) mice) were used to develop a method for P-glycoprotein (P-gp) function imaging non-invasively and to study the eect of a P-gp reversal agent on its function in vivo. ]verapamil accumulation in the brain of mdr1a(+/+) mice was increased by cyclosporin A to levels comparable with those in mdr1a(7/7) mice, indicating that reversal of P-gp mediated eux can be monitored by PET. 5 We conclude that cyclosporin A can fully block … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
112
1
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 170 publications
(128 citation statements)
references
References 28 publications
11
112
1
2
Order By: Relevance
“…Western blot analysis performed in spinal cord homogenates of SOD1-G93A mice showed that immunoreactivity for P-gp remarkably increased during progression of the disease compared to age-matched SOD1-wild type mice (Fig.6 upper and lower panels) or even nontransgenic mice (not shown), suggesting that these drug efflux transporters are markedly upregulated in the ALS mice. We also found that similar to Verapamil, a known substrate for Pgp (Langer et al, 2007;Hendrikse et al, 1998), NDGA modulates the activity of P-gp in isolated membrane vesicles (Table 1) (Seelig, 1998). Although this assay does not provide direct evidence that NDGA can be transported by P-gp, the modulation of P-gp activity strongly indicated that NDGA could serve as substrate for this transporter (Garrigues et al, 2002).…”
Section: Increased Expression Levels Of P-glycoprotein Transporters Imentioning
confidence: 83%
See 1 more Smart Citation
“…Western blot analysis performed in spinal cord homogenates of SOD1-G93A mice showed that immunoreactivity for P-gp remarkably increased during progression of the disease compared to age-matched SOD1-wild type mice (Fig.6 upper and lower panels) or even nontransgenic mice (not shown), suggesting that these drug efflux transporters are markedly upregulated in the ALS mice. We also found that similar to Verapamil, a known substrate for Pgp (Langer et al, 2007;Hendrikse et al, 1998), NDGA modulates the activity of P-gp in isolated membrane vesicles (Table 1) (Seelig, 1998). Although this assay does not provide direct evidence that NDGA can be transported by P-gp, the modulation of P-gp activity strongly indicated that NDGA could serve as substrate for this transporter (Garrigues et al, 2002).…”
Section: Increased Expression Levels Of P-glycoprotein Transporters Imentioning
confidence: 83%
“…It is therefore likely that the lack or loss of the NDGA efficacy in these mice could be consequential to its increased extrusion from the CNS, and the spinal cord in particular, due to the increased expression levels of P-gp proteins. The membrane assay we employed showed that NDGA interacts with P-gp as strongly as another known transported substrate structurally similar, verapamil (Langer et al, 2007;Hendrikse et al, 1998), suggesting that NDGA could be a substrate for these drug efflux transporters. This assay cannot accurately answer the question whether the tested compound that interacts with P-gp could also be a substrate for the drug transporter.…”
Section: Discussionmentioning
confidence: 99%
“…11 C]verapamil as P-gp substrate in patients (Hendrikse et al, 1998(Hendrikse et al, , 1999Bart et al, 2003Bart et al, , 2005Syvanen et al, 2006;Takano et al, 2006). Future studies should elucidate if these results can be extrapolated to the human setting.…”
Section: Discussionmentioning
confidence: 99%
“…At present the concept of efflux pump inhibition is most frequently studied for P-gp. Studies in rodents have shown that P-gp function can be inhibited with cyclosporin A (CsA) (Hendrikse et al, 1998(Hendrikse et al, , 1999Syvanen et al, 2006). To circumvent toxic side effects of CsA in patients, therapies that influence P-gp function could be utilised, such as radiotherapy.…”
mentioning
confidence: 99%
“…Verapamil and cyclosporine are often used as P-gp inhibitors. However, these agents are also substrates of P-gp and inhibit P-gp activity in a competitive manner, 26,27 suggesting that the degree of inhibition of P-gp depends on the concentration ratio of inhibitors and substrates. The concentrations of these inhibitors required to inhibit P-gp-dependent transport of local anesthetics are unknown, since no data are available regarding the inhibition constants of these inhibitors.…”
Section: Measurement Of Lidocaine Megx and Bupivacaine In Plasma Andmentioning
confidence: 99%